Implementation of Pancasila Student Profile in the Merdeka Curriculum For High School in Sragen Regency - Laila, Rahma Nur; Assunniyah, Nada; Nugroho, Nur Sulis Adi; Permata Sari, Ratih Gusti; Suwandi, Sarwiji; Setiyoningsih, Titi (Al Hikmah: Journal of Education, 2022)
The independent curriculum is a curriculum renewal that was launched directly by the Minister of Education & Culture, Nadiem Makarim with all considerations made for more than 4-5 years. This curriculum is something new for school residents, especially teachers who teach so that it requires preparation in any way to maximize the application of an independent curriculum in educational units. The independent curriculum was launched in the form of a learning design that provides opportunities for students to learn without pressure according to their potential, while also focusing more on developing the freedom to think innovatively and creatively. In the independent curriculum-based learning process, the Pancasila student profile which consists of six dimensions is a reference for educators and students in schools. In Sragen Regency, there are several schools, especially the secondary school level, which have implemented the Pancasila student profile. This research to determine the profile of Pancasila students at the secondary school level. This research uses descriptive qualitative method with a case study approach. After conducting research and obtaining sufficient data, it is known that there are at least two schools that have implemented an independent curriculum since the previous academic year with some preparations to maximize the implementation of the Pancasila student profile in the midst of existing obstacles.